OUTBOUND TRAINING SEBAGAI SALAH SATU METODE PENDIDIKAN PENGUATAN SDM - Kusuma, Yuga Adi (Institut Agama Islam Syarifuddin Lumajang, 2018)
Human Labor is a decisive factor because humans, which are one of the production aspects, have a role in establishing development. Human Resources are the main assets in all activities within the community. The right training and education such as outbound training will improve the quality of human resources.